Riotous Deathscapes and New Psychologies: Toward Ecoscapes of Decolonial Desire - Dutta, Urmitapa (PINS-Psychology in Society, 2024)
Ka Canham, H. (2023). Riotous Deathscapes. Duke University Press. 228 pages. E-ISBN: 978-1-4780-1959-6 Hardcover ISBN978-1-4780-2422-4